2013
DOI: 10.11648/j.nano.20130102.12
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon Nanoparticles from Kerosene and their Characterization by SEM⁄EDX, XRD and FTIR

Abstract: Carbon nanoparticles (CNPs) were synthesized by a simple way of incomplete combustion of kerosene. Synthesized nanoparticles were characterized by Scanning electron microscope (SEM), Energy dispersive x-ray (EDX), Powder x-ray diffractometry (XRD) and Fourier transform infrared spectroscopy (FTIR). The SEM particle sizes of prepared CNPs were found to be non-uniform. The average size of particles is in the range of 20-100 nm. EDX analysis predicts the presence of pure carbon without any contamination. X-ray po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…A single particle of size 80 nm was successfully isolated in the AFM measurement. This result is similar with the SEM observation (Hossain et al, 2013). Van der Pauw Hall effect measurement system and source meter were used to investigate the electrical property of carbon nanoparticles.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…A single particle of size 80 nm was successfully isolated in the AFM measurement. This result is similar with the SEM observation (Hossain et al, 2013). Van der Pauw Hall effect measurement system and source meter were used to investigate the electrical property of carbon nanoparticles.…”
Section: Resultssupporting
confidence: 82%
“…The slight deviation from the expected value indicated that a small amount of amorphous carbon was present in this sample. However, the prepared carbon nanoparticles are about 72% pure, which was proved in the EDX analysis of the prepared carbon nanoparticles sample (Hossain et al, 2013…”
Section: Tga Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…4. The profile shows two peaks at 2θ of 23.85° and 26.55°(with interlayer spacing 3.73Å and 3.36Å calculated according to the Bragg's equation) corresponding to the amorphous and the graphitic nature of the resulted product (JCPDS Code: 00-008-0415) as also described earlier in the literature [14,[17][18][19][20][21][22][23][24]. The mean size of the crystalline CMBs was also calculated from the major diffraction peak using the Scherrer formula which was found to be 40.59 nm.…”
Section: X-ray Diffractometrysupporting
confidence: 57%
“…The highest peak of amorphous carbon intensity obtained in samples with non-oxidative heat treatment. CNTs produced at peak 43° is MWCNT with low quality nanomaterials [15]. Thereby, hexagonal graphite also formed at peak 43.7°.…”
Section: Synthesis Of Carbon Nanotube With Vertical Structured Gauze mentioning
confidence: 97%